Cloning and characterization of the wheat domestication gene, Q - Simons, Kristin Jean (Kansas State University, 2005)
The Q gene is largely responsible for the widespread cultivation of durum and common wheat because it confers the square spike phenotype and the free-threshing character. It also pleiotropically influences many other domestication related traits such as glume shape, glume tenacity, rachis fragility, spike length, plant height, and spike emergence time. The objectives of this research were to confirm or reject the hypothesis that a candidate AP2-like gene is Q, confirm the dosage and pleiotropic effects attributed to Q, and begin defining the differences between the Q and q alleles. The identity of the Q gene was verified by analysis of knockout mutants and found to have a high degree of similarity to members of the AP2 family of transcription factors. Southern analysis of multiple Triticum taxa containing either Q or q indicated that the Q locus is not composed of duplicated q alleles. Ectopic expression analysis allowed the observation of both silencing and over-expression effects of Q. Rachis fragility, glume shape, and glume tenacity mimicked the q phenotype in transgenic plants exhibiting transcriptional silencing of the transgene and the endogenous Q gene. Variation in spike compactness and plant height were directly associated with the level of transgene expression due to the dosage effects of Q. Comparisons of Q and q indicated structural differences as well as variation in the level of transcription. One amino acid difference and several base changes within the promoter were identified as possible critical differences between Q and q. Very little genetic variability was found within the sequenced Q alleles suggesting it arose only once and that q is the more primitive allele.
Keywords: Wheat; Domestication; Floral morphology; APETELA2; Biology, Genetics (0369); Biology, Molecular (0307)